A Review of the Humoral Terminology in Romania - Pavel, Ecaterina (Philologica Jassyensia, 2021)
The purpose of this paper is to provide an overview of the terminology designating humours as it appears in Romania. From medicine to literature, from the Hippocratic theory of the four humours (umori) to the etymological doublet umor, this research paper will investigate the semantic and onomasiological fluctuations of three lexical fields: umoare (fluid), umoare (temperament) and umor (humour). The study does not aim to provide a comprehensive inventory of the terms (and their contexts) belonging to these semantic categories, but to identify the terms denoting the three concepts and their evolution in the Romanian language in its process of modernisation.
Keywords: humours; humour; humorism; temperament; Hippocratic terminology